2018
DOI: 10.3847/1538-4357/aab08f
|View full text |Cite
|
Sign up to set email alerts
|

Early-type Galaxy Spin Evolution in the Horizon-AGN Simulation

Abstract: Using the Horizon-AGN simulation data, we study the relative role of mergers and environmental effects in shaping the spin of early-type galaxies (ETGs) after z 1. We follow the spin evolution of 10,037 color-selected ETGs more massive than 10 10 M that are divided into four groups: cluster centrals (3%), cluster satellites (33%), group centrals (5%), and field ETGs (59%). We find a strong mass dependence of the slow rotator fraction, f SR , and the mean spin of massive ETGs. Although we do not find a clear en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 69 publications
8
31
0
Order By: Relevance
“…Most galaxies, regardless of their stellar mass, show a decrease in V θ /σ after infall, as also demonstrated in Gnedin (2003b), Choi & Yi (2017) and Choi et al (2018). At a given mass, galaxies with higher Φ/∆t have V θ /σ smaller than those with lower Φ/∆t at both z = 0 and z infall .…”
Section: Stability Of Spin Vectors and V θ /σsupporting
confidence: 58%
“…Most galaxies, regardless of their stellar mass, show a decrease in V θ /σ after infall, as also demonstrated in Gnedin (2003b), Choi & Yi (2017) and Choi et al (2018). At a given mass, galaxies with higher Φ/∆t have V θ /σ smaller than those with lower Φ/∆t at both z = 0 and z infall .…”
Section: Stability Of Spin Vectors and V θ /σsupporting
confidence: 58%
“…However, tidal interactions (or fly bys) between galaxies can produce similar effects to that due to actual mergers (e.g. Martin et al 2018a;Choi et al 2018). To explore the effect of tidal interactions on LSBGs and HSBGs, we employ a perturbation index (PI) which quantifies the environmental tidal field due to objects in the vicinity of the galaxy in question.…”
Section: Perturbations Due To the Ambient Tidal Field -A Key Driver Omentioning
confidence: 99%
“…Thus we have the ability to unveil new and important shortcomings of the simulations. Ellipticity has been explored in combination with V/σ and λ R (e.g., Naab et al 2014;Penoyre et al 2017;Choi et al 2018;Lagos et al 2018b;Schulze et al 2018), but here we have taken an additional step of comparing ellipticity distributions using massmatched samples. The offset towards thicker disks in eagle was also noticed by Trayford et al (2017) who found that the optical extinction is much smaller than observed for edge-on galaxies, but consistent for face-on objects.…”
Section: Comparing Observations and Simulations With Eagle Horizon-amentioning
confidence: 99%
“…The success of such an approach has already been demonstrated by Naab et al (2014), Welker et al (2017), Remus et al (2017), Penoyre et al (2017), Choi & Yi (2017), Choi et al (2018), Lagos et al (2018a,b), and Martin et al (2018). Naab et al (2014) use cosmological hydrodynamical zoom-in simulations of 44 individual central galaxies, and link the assembly history of these galaxies to their stellar dynamical features.…”
mentioning
confidence: 99%